Experimental Investigation on Juncture Flow Associated with a Surface-Mounted Circular Cylinder Trailed by a Backward-Facing Step - Chun-Yao Yang; Yi-Chih Chow (Journal of Marine Science and Engineering, 2022)
Juncture flows associated with surface-mounted obstacles can be characterized by a U-shaped tubular vortical flow known as a horseshoe vortex (HSV). Horseshoe vortices are usually detrimental to engineering applications. In order to identify a boundary geometry that may effectively reduce a HSV’s strength for further design of HSV-reduction devices, or otherwise enhance it for further disaster prevention by avoiding such a geometry in design, the characteristics of HSVs influenced by external boundary geometries must first be understood. Thus, we experimentally investigated a juncture flow field associated with a fundamental geometry—a circular cylinder mounted perpendicular to a plane surface—with a trailing backward-facing step (BFS) representing a novel idea of downstream effects on upstream-formed flow structures. This setup is not only one of the simplest nonplanar geometries that generates flow features such as an unsteady separated shear layer that may considerably affect an HSV, but it is also a new attempt without prior knowledge. We used the particle image velocimetry (PIV) and PIV-based flow visualization techniques combined with a vortex-fitting algorithm to measure the juncture flow and identify the HSV and its kinematic modes at the low Reynolds number of 1166. We observed from the flow-visualization results regarding HSV’s kinematic modes and their duration percentages as follows: (1) without the BFS: “oscillation with a small displacement” (98.6%) and “breakaway to roll-up” (1.4%); (2) with the BFS (step height/cylinder diameter = 1.5): “oscillation with a small displacement” (83.3%), “merging” (4.5%), and “mixed” (12.2%). It is clearly evident that the BFS increased the number and complexity of kinematic modes, i.e., the unsteadiness of the HSV. Moreover, the PIV results show that the BFS reduced HSV stretching, which resulted in increased vortex diameter by 8.24% and increased circulation by 6.37%, i.e., the strength of the HSV was enhanced by the BFS.